PELATIHAN KOMUNIKASI INTERPERSONAL UNTUK MENINGKATKAN KOMITMEN ORGANISASI KARYAWAN - Gusfika, Nira (Al-Qalb : Jurnal Psikologi Islam, 2018)
This study aims to determine the improvement of organizational commitment through interpersonal communication training. The hypothesis of this research is that there is a difference of organizational commitment to employees between before and after being given interpersonal communication training on experimental group, where the level of commitment of employee organization after being given interpersonal communication training is higher than the level of organizational commitment of the employees before being given interpersonal communication training. Second hypothesis, there is difference of posttest organizational commitment level between experiment group and control group, where posttest of organizational commitment in experiment group is higher than control group.The subject of this research is 17 employees at STAI YAPPTI Balaiselasa. Characteristics of the subjects of this study are employees who have levels of organizational commitment and interpersonal communication in the category very low, low and medium. The design used was Pretest-Posttest Control Group, while the data was collected using organizational commitment scale then analyzed using Mann Whitney test to see the difference of score between the experimental group who were given interpersonal communication training with the control group who were not given interpersonal communication training. Furthermore, Wilcoxon test was done for see experimental group scores between before and after interpersonal communication training.Based on Mann Whitney test results found Z = -3.447 (p <0.01), meaning there is a difference in scores between experimental groups who were trained with control groups who were not trained. Based on Wilcoxon test results found there was a difference between organizational commitment score in the experimental group between before and after being given interpersonal communication training with Z = -2,668 (p<0,01).